2011
DOI: 10.1108/09513551111163639
|View full text |Cite
|
Sign up to set email alerts
|

Clashes as potential for innovation in public service sector reform

Abstract: Purpose -The purpose of this study is to examine the ongoing dynamics of the public service sector reform through an embedding process of a municipal enterprise from the field of basic social and health care services -a pilot model in Finland. Design/methodology/approach -The framework of a multi-level perspective on transitions is used to describe the change process. At the lowest level of this perspective are the experimental niches acting as "seeds of change" represented by the case organisation, a municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…In his research, Kim [9] revealed that managerial quality is the main element of innovation, so it cannot be ignored even though it fluctuates. Japanese and American practices influence the quality of management (innovation) in Korea, and the influence of European management is not so visible in practice [10]. Palm and Algehed [11] in the article Exploring Enablers of Innovative Quality Development in Public Administration.…”
Section: Earlier Researchmentioning
confidence: 99%
“…In his research, Kim [9] revealed that managerial quality is the main element of innovation, so it cannot be ignored even though it fluctuates. Japanese and American practices influence the quality of management (innovation) in Korea, and the influence of European management is not so visible in practice [10]. Palm and Algehed [11] in the article Exploring Enablers of Innovative Quality Development in Public Administration.…”
Section: Earlier Researchmentioning
confidence: 99%
“…Which neural processes determine whether a visual stimulus will be consciously perceived? Examples of theoretical attempts to answer such question include the global workspace model (GWT; Baars, 1988;Dehaene & Changeux, 2011), integrated information theory of consciousness (IIT; Oizumi, Albantakis, & Tononi, 2014), and higher-order thought theory of consciousness (Lau & Rosenthal, 2011). These theories aim to describe how consciousness "emerges" from neural activity.…”
Section: Lower-level Constituentsmentioning
confidence: 99%
“…Consider the GWT, for example. According to the theory, consciousness is a process where a large number of individual modules share their information with each other to enable flexible behavior and maintenance of information (Baars, 1988). According to the neural model of the theory, this corresponds to synchronous interactions between specific neural populations in frontal, parietal and sensory cortical areas (Dehaene & Changeux, 2011).…”
Section: Lower-level Constituentsmentioning
confidence: 99%
“…Since the 1980s, cities and other public organizations have been affected by a range of new management models and structures labelled new public management (NPM), and interest in innovation could be said to stem from this development (Bartlett and Dibben, 2002;De Vries and Nemec, 2013). Innovation in public-sector organizations has been studied in sectors such as health care (Pekkarinen et al, 2011), education (Baldridge and Burnham, 1975), and, as is the case here, city planning (Shearmur, 2012).…”
Section: Introductionmentioning
confidence: 99%